KOMPETENSI PEDAGOGIK DAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK - Fitra Fengki Arista (UNISAN JURNAL, 2024)
This examination plans to investigate the job of academic skill and incredible skill of Al Qur’an Hadith educators in beating understudies’ learning challenges at SMP Negeri 02 Buay Pemuka Peliung. The exploration technique utilized is subjective with a contextual investigation approach. Information was gathered through inside and out interviews with Al Qur’an Hadith instructors, study hall perceptions, and archive investigation. The consequences of the examination show that the Al Qur’an Hadith instructor at SMP Negeri 1 Saling has a profound comprehension of the educational program and learning strategies that suit the necessities of understudies. They utilize different imaginative and inventive learning procedures to beat understudies’ learning troubles, including the utilization of mixed media, bunch conversations, and involved useful exercises. Aside from that, these educators likewise show an elevated degree of impressive skill in treating every understudy exclusively, offering the ethical help and inspiration required, and cooperating with guardians and other school staff to work on understudies’ scholarly execution. These discoveries delineate the significance of academic ability and amazing skill in working on the nature of Al Qur’an Hadith learning and beating understudies’ learning hardships in optional schools. The reasonable ramifications of this examination are the requirement for proceeded with help for the improvement of Al Qur’an Hadith educator capabilities, as well as a more noteworthy job for schools in working with the trading of information and best practices between instructors. Further exploration can investigate different elements that impact the adequacy of showing Al Qur’an Hadith and methodologies that can be carried out to further develop understudy learning results.